RAPD markers linked to sex in the genus Pistacia - Kafkas S.; Cetiner M.S.; Perl-Treves R. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Leaf samples were collected from ten male and ten female trees from P. atlantica, P. terebinthus, P. eurocarpa species. Sex-pooled DNA samples were prepared by mixing the DNA of ten male and ten female individuals, respectively. Among all the 312 primers screened so far, three bands, amplified by primers OPL11 and BC152 appeared to be sex correlated in P. terebinthus and three bands amplified by primers BC156 and BC360, appeared to be sex correlated in P. eurocarpa. The results showed that in each of the putative sex-related bands, the correlation with sex is only partial, and some individuals have the marker-phenotype of the opposite sex. It is possible that the marker is linked to a sex-determining locus but not very tightly. We also observed that many of the RAPD bands screened in this experiment can be identified as species-specific. Additional male female individuals were sampled and their testing is underway.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)